2012
DOI: 10.1007/s00402-012-1551-2
|View full text |Cite
|
Sign up to set email alerts
|

The optimal carrier for BMP-2: a comparison of collagen versus fibrin matrix

Abstract: We conclude that fibrin matrix is an excellent carrier for BMP-2 and that it provides equivalent results with a sevenfold lower dose of BMP-2 compared with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…BMPs induced MSCs to migrate to bone-forming sites, differentiate into an osteoblast lineage, and regenerate bone. 157 Local pharmacokinetics are very important for the therapeutic efficacy of BMPs. For example, when …”
Section: Bmp Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…BMPs induced MSCs to migrate to bone-forming sites, differentiate into an osteoblast lineage, and regenerate bone. 157 Local pharmacokinetics are very important for the therapeutic efficacy of BMPs. For example, when …”
Section: Bmp Deliverymentioning
confidence: 99%
“…158 Besides this minimal effect, the rapid release of BMP-2 can cause adverse effects and will require more frequent administration which is costly. 157 Therefore, it is necessary to develop a delivery system that can release BMPs locally for a sufficient time period and concentration. Among several different BMP carriers, a fibrin matrix is considered as an excellent carrier.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is absorbable and supports angiogenic ingrowth. 55,56 In this study, soaking the scaffolds with fibrin resulted in inferior results when compared with autologous serum and cell culture medium, possibly due to the special nanostructured architecture. Comparison of the two combination groups with expanded MSC and rhBMP-2 in fibrin and serum demonstrated that fibrin is not crucial for the delivery of the growth factor BMP-2 over time.…”
Section: New Bone Formation Depending On Implanted Cells and Carrier mentioning
confidence: 70%